O. Hashimov’s Artistic Interpretation of the Character of the Teacher in "Between Two Doors" - Soberova, Mohira (FILOLOGIYA UFQLARI JURNALI, 2024)
This article discusses the artistic interpretation of the themes of teaching and enlightenment in the novel "Between Two Doors".